2008
DOI: 10.1017/s0022112008000773
|View full text |Cite
|
Sign up to set email alerts
|

A stationary circular hydraulic jump, the limits of its existence and its gasdynamic analogue

Abstract: We propose a theory of a steady circular hydraulic jump based on the shallow-water model obtained from the depth-averaged Navier–Stokes equations. The flow structure both upstream and downstream of the jump is determined by considering the flow over a plate of finite radius. The radius of the jump is found using the far-field conditions together with the jump conditions that include the effects of surface tension. We show that a steady circular hydraulic jump does not exist if the surface tension is above a ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
98
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(103 citation statements)
references
References 11 publications
5
98
0
Order By: Relevance
“…The results presented are for parameters, Q = 5, K i = 1, K r = 2 and ν = 0.5. Below the critical value α = 5.7, the steady solution is stable, and propagated with the steady wave structure given above at its constant CJ speed given by (6). Above this critical value the travelling wave solution is unstable and develops a stable limit-cycle, as shown in Fig.…”
mentioning
confidence: 80%
“…The results presented are for parameters, Q = 5, K i = 1, K r = 2 and ν = 0.5. Below the critical value α = 5.7, the steady solution is stable, and propagated with the steady wave structure given above at its constant CJ speed given by (6). Above this critical value the travelling wave solution is unstable and develops a stable limit-cycle, as shown in Fig.…”
mentioning
confidence: 80%
“…This equation has a regular solution crossing the sonic point c = u provided / = 0 at the same point, which is precisely Figure 9: Left -comparison between our theoretical prediction of the hydraulic jump structure [9] and experiment. Right -jamiton profile in the theory of traffic shocks [7J.…”
Section: Development Of Detonation Analogsmentioning
confidence: 53%
“…Two of such phenomena, a circular hydraulic jump [9] and a traffic jam [7], have been investigated in detail. It was shown that both in traffic jam and the hydraulic jump, the theory of the steady solution is similar to the Zel'dovich-von Neumann-Doering theory of detonation [6].…”
Section: Development Of Detonation Analogsmentioning
confidence: 99%
See 2 more Smart Citations